The application of quasi-enantiomeric trianglamine macrocycles as chiral probes for anion recognition in ion trap ESI mass spectrometry - Kuhnert, Nikolai; Marsh, David; Nicolau, Daniel C. (Tetrahedron: asymmetry, 2007)
This paper reports the synthesis and application of quasi-enantiomeric trianglamine macrocycles for chiral analysis using ion trap ESI mass spectrometry. The quasi-enantiomeric macrocycles were shown to display chiroselection towards a series of enantiomerically pure carboxylic acids and therefore act as chiral probes for anions in the gas phase and in solution.